Study of electrical properties and detection mechanism of a practical novel 3D-Spherical Electrode Detector - Tan, Zewen; Li, Zheng; Li, Xinqing; Cai, Xinyi; Liu, Manwen; Wang, Hongfei (Frontiers in Materials, 2023)
Among the 3D electrode Si detectors for high energy particle and X-ray detection, the traditional 3D-Trench electrode Si detector is a semiconductor detector that is widely used and discussed. Aiming at removing the shortcomings of the traditional 3D-Trench electrode Si detectors such as uneven electric field distribution, asymmetric electric potential, and the existence of some dead zone, we propose a new type 3D-Spherical Electrode Detectors and carry out extensive and systematic studies of their physical properties. We simulated detector electric field, electric potential, electron concentration distribution, full depletion voltage, leakage current, capacitance, the incident partcle induced transient current and the weighting field. We and systematically studied and analyzed detector's electrical characteristics. By comparison, the performance of the new detector structure is better than that of the traditional 3D-Trench electrode Si detectors.